Assessing Core-powered Mass Loss in the Context of Early Boil-off: Minimal Long-lived Mass Loss for the Sub-Neptune Population - Yao Tang; Jonathan J. Fortney; Ruth Murray-Clay (The Astrophysical Journal)
We develop a Python-based state-of-the-art sub-Neptune evolution model that incorporates both the post-formation boil-off at young ages ≤1 Myr and long-lived core-powered mass loss (∼Gyr) from interior cooling. We investigate the roles of initial H/He entropy, core luminosity, energy advection, radiative atmospheric structure, and the transition to an X-ray- and ultraviolet-driven mass-loss phase, with an eye on relevant timescales for planetary mass loss and thermal evolution. With particular attention to the re-equilibration process of the H/He envelope, including the energy sources that fuel the hydrodynamic wind, and energy transport timescales, we find that boil-off and core-powered escape are primarily driven by stellar bolometric radiation. We further find that both boil-off and core-powered escape are decoupled from the thermal evolution. We show that, with a boil-off phase that accounts for the initial H/He mass fraction and initial entropy, post-boil-off core-powered escape has an insignificant influence on the demographics of small planets, as it is only able to remove at most 0.1% of the H/He mass fraction. Our numerical results are directly compared to previous work on analytical core-powered mass-loss modeling for individual evolutionary trajectories and populations of small planets. We examine a number of assumptions made in previous studies that cause significant differences compared to our findings. We find that boil-off, though able to completely strip the gaseous envelope from a highly irradiated ( F ≥ 100 F _⊕ ) planet that has a low-mass core ( M _c ≤ 4 M _⊕ ), cannot by itself form a pronounced radius gap as is seen in the observed population.